Long-term Remission of Severe and Refractory Chronic Actinic Dermatosis with Dupilumab: A Case Report with Review of the Literature - Clélia Vanhaecke; Manuelle Viguier (Medical Journals Sweden, 2024)
Abstract is missing (Short communication)